Biomechanical Study between the Rigid and Dynamic Fixation Systems of the Spinal Column Analyzed by the Finite Element Method - Samir Zahaf; Said Kebdani (Nano Biomedicine and Engineering, 2017)
Orthopedic fixation devices are widely used in treatment of spinal diseases. It is expected that application of dynamic stabilization confers valuable movement possibility besides its main role of load bearing. Comparative investigation between pedicle screw model rigid fixation and (B Dyne, Elaspine, Bioflex, Coflex rivet) models dynamic fixation systems may elucidate the efficacy of each design. The goal of the present study is to evaluate the efficacy of five fixation systems mounted on L4-L5 motion segment. In this numerical study, a 3D precious model of L4, L5 and their intervertebral disc has been employed based on CT images. Five fixation devices have been also implanted internally to the motion segment. Finite element method was used to evaluate stress distribution in the disc and determine the overall displacement of the segment as a measure of movement possibility. The results show that the Coflex rivet implantation can provide stability in all motions and reduce disc annulus stress at the surgical segment L4-L5. On the other hand, maximum stress in the disc has been observed in dynamic systems but within the safe range. The greater movement of the motion segment has also appeared in dynamic fixations. Existence of the fixation systems reduced the stress on the intervertebral disc which might be exerted in intact cases. Use of the fixation devices can considerably reduce the load on the discs and prepare conditions for healing of the injured ones. Furthermore, dynamic modes of fixation confer possibility of movement to the motion segments in order to facilitate the spinal activities.